A method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials

By calculating the gel risk index and quickly judging the appropriate amount of pulping and acid addition, the problem of difficult to control the amount of acid addition in pulping of sodium-electrode positive electrode layered oxide materials is solved, avoiding the risk of gelation, and improving the preparation efficiency and quality.

CN119763733APending Publication Date: 2025-04-04TIANJIN ZHONGDIAN NEW ENERGY RES INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411678128.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the pulping process of sodium-electrode layered oxide materials, it is difficult for the prior art to accurately control the amount of acid added, resulting in the possibility of gelation of the slurry, affecting battery performance and coating effect.

Method used

By detecting the moisture content, fine powder rate and pH of the positive electrode active material, combining the homogenization amount, the gel risk index is calculated, and the appropriate amount of pulping and acid addition is quickly judged to antagonize the gelation trend.

Benefits of technology

The rapid and accurate judgment of the amount of acid added to the pulping is achieved, the risk of gelation is avoided, and the preparation efficiency and quality of sodium-electrode positive layered oxide materials are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for quickly judging the amount of acid added in the pulping of sodium positive electrode layered oxide materials, and the steps include: predicting the slurry gel risk based on risk factors, the risk factors include: the amount of homogenization, and the moisture content, fine powder rate and pH of the positive electrode active material; judging the amount of acid added in the pulping based on the slurry gel risk, the amount of acid added in the pulping = the mass of the positive electrode active material × the recommended acid value, and the recommended acid value is ≤0.8%. The present invention provides a method for quickly predicting the slurry gel risk and judging the amount of acid added in the pulping in large-scale pulping of sodium positive electrode layered oxide materials, which is used to antagonize the gelation trend of the positive electrode slurry and prevent excessive acid from affecting the electrical properties of the positive electrode active material and the coating effect of the positive electrode slurry; the method does not need to use the traditional titration method for measuring residual alkali or small batch homogenization test, but only needs to perform basic physical property tests, thereby improving the preparation efficiency and quality of the sodium positive electrode layered oxide material slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pulping of sodium positive electrode layered oxide materials, and in particular to a method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials. Background Art

[0002] In the process of manufacturing sodium-ion battery pole pieces, slurry preparation is a key process in the front stage. The slurry characteristics have an important impact on the subsequent coating, rolling and other processes as well as the final sodium-ion battery performance. The slurry generally contains active materials, binders, conductive agents and solvents. Among them, the state of the binder greatly affects the fluidity of the slurry, which in turn affects the coating quality.

[0003] For the slurry with sodium-based layered transition metal oxide as the positive electrode active material, since there is residual sodium salt on the surface of the sodium-based layered transition metal oxide, the sensitivity of the sodium-based layered transition metal oxide to humid air is increased, and the sodium in the sodium-based layered transition metal oxide is further reacted with water and carbon dioxide in the environment, resulting in the formation of more sodium hydroxide and sodium salt. The formation of these sodium hydroxide and sodium salt not only increases the impedance of the positive electrode and reduces the electrochemical stability of the battery, but also leads to the enhancement of the alkalinity of the slurry, promoting the defluorination reaction of polyvinylidene fluoride (binder) through nucleophilic reaction to form a cross-linked conjugated polyene, causing the slurry to gel and reduce the fluidity of the slurry.

[0004] At present, the industry usually adopts the method of pre-acidification to avoid gelation of the slurry during the pulping process. Although adding acid can avoid the gelation problem, whether the slurry will gel is affected by many factors, such as the amount of homogenization, the amount of residual alkali in the material, the moisture content, the particle size distribution, etc., which greatly increases the difficulty of accurately controlling the amount of acid added. Adding too little acid is not enough to antagonize the gelation trend of the slurry and reduce the processing performance. Adding too much acid will reduce the electrochemical properties of the material and may also affect the coating effect.

[0005] Some manufacturers use expensive acid-base titration equipment or manual titration to test the residual alkali content of materials, or conduct small-batch homogenization experiments to calculate the amount of acid to be added or determine whether the amount of acid to be added is appropriate. However, the manual titration method for measuring residual alkali is affected by experience and is difficult to guarantee accuracy. The small-batch homogenization test method is time-consuming and costly. Therefore, developing a fast, accurate, and reliable method for determining the amount of acid to be added for pulping is of great significance for improving the preparation efficiency and quality of sodium cathode layered oxide material slurry. Summary of the invention

[0006] The purpose of the present invention is to provide a method for quickly judging the amount of acid added in the pulping of sodium positive electrode layered oxide materials, so as to solve the problems existing in the background technology.

[0007] The technical solution of the present invention is: a method for quickly judging the amount of acid added in the slurry of sodium-based positive electrode layered oxide materials. The method is used to quickly predict the risk of gelation during the homogenization process of positive electrode slurry with sodium-based layered transition metal oxide as positive electrode active material, and quickly judge the appropriate amount of acid added in the slurry to antagonize the gelation trend of the positive electrode slurry and avoid excessive acid affecting the performance of the positive electrode active material and the coating effect of the positive electrode slurry. The steps specifically include S1 and S2.

[0008] S1. Predict the slurry gel risk based on risk factors, including: slurry volume, and the moisture content, fine powder rate and pH of the positive electrode active material.

[0009] The amount of homogenization affects the dispersion efficiency of each component in the positive electrode slurry during the homogenization process. Due to the nature of the binder itself, when the stirring speed reaches a certain level, the time for the binder to fully dissolve no longer decreases with the increase in stirring speed (PVDF takes about three hours), and too fast stirring speed will also destroy the structure of the binder and the positive electrode active material and change its original performance. Therefore, at an appropriate and determined stirring speed (referring to not destroying the original structural performance of the slurry components), the larger the amount of homogenization, the slower the dispersion of each component in the positive electrode slurry, the positive electrode active material is concentrated in one corner, resulting in excessive alkalinity in the local positive electrode slurry, and the greater the risk of PVDF defluorination and conjugated cross-linking, that is, the greater the risk of local preferential gelation of the positive electrode slurry. Although this gelation is local, it is a chemical gelation transformation, which cannot be solved by accelerating stirring and extending stirring time. It will only gradually spread and increase in a chain until the entire positive electrode slurry undergoes gelation transformation.

[0010] The positive electrode active material, namely the sodium-based layered transition metal oxide, after high-temperature calcination during the preparation process, the sodium ions gradually lose their activity during natural cooling, reacting with carbon dioxide and oxygen in the atmosphere to form amorphous sodium carbonate on the surface of the positive electrode active material. These amorphous sodium carbonates increase the sensitivity of the positive electrode active material to humid air, and the sodium-based layered transition metal oxide has a high surface polarity, which causes water molecules to be physically or chemically adsorbed on its surface, resulting in the spontaneous extraction of sodium ions from the lattice (usually through Na / H + / H3O + Exchange mechanism), further reacting with water and carbon dioxide in the environment to form more sodium hydroxide and sodium carbonate, and the particle size of the positive electrode active material will also affect the rate of the above-mentioned side reactions, which will lead to an increase in the residual alkali content of the material and an increase in the risk of further reaction of sodium ions in the material with water and carbon dioxide in the environment during homogenization, thereby promoting the gelation transformation of the positive electrode slurry.

[0011] In this step, the moisture content, fine powder rate and pH of the positive electrode active material are detected, and homogenization tests are carried out at different homogenization amounts to explore and verify, so as to evaluate the differentiated effects of changes in various risk factors on the risk of gelation transformation of the positive electrode slurry, as well as the comprehensive effects of all risk factors on the gelation transformation of the positive electrode slurry, so as to quantify the contribution of changes in various risk factors to the risk of gelation transformation of the positive electrode slurry, and then obtain indicators that can quickly predict the gelation risk of the slurry, namely the gel risk index and the gel risk value of each risk factor.

[0012] In the present invention, the gel risk index is equal to the sum of the gel risk values ​​of each risk factor. According to the percentage division method, the lower limit of the gel risk value of each risk factor is set to 0, and the upper limit is set to 25. According to the gel transformation verification test results of the positive electrode slurry, that is, the degree to which the actual gel risk of the slurry changes due to the change of each risk factor, the actual value of each risk factor and the gel risk value are hierarchically divided and matched, and the following content is obtained.

[0013] For the homogenate volume, if the homogenate volume is ≤570L, the gel risk value is an even number less than 25; if the homogenate volume is >570L, the gel risk value is 25.

[0014] More specifically, they include: when the homogenate volume is ≤10L, the gel risk value is 0; when the homogenate volume is ≤170L, the gel risk value increases by 4 for every 80L increase in the homogenate volume; when the homogenate volume is 170L<≤250L, the gel risk value is 16; when the homogenate volume is ≤570L, the gel risk value increases by 2 for every 80L increase in the homogenate volume; and when the homogenate volume is >570L, the gel risk value is 25.

[0015] More specifically, they include:

[0016] When the homogenate volume is ≤10L, the gel risk value is 0;

[0017] When the homogenate volume is 10L≤90L, the gel risk value is 4;

[0018] When the homogenate volume is 90L≤170L, the gel risk value is 8;

[0019] When the homogenate volume is 170L≤250L, the gel risk value is 16;

[0020] When the homogenate volume is 250L≤330L, the gel risk value is 18;

[0021] When the homogenate volume is 330L≤410L, the gel risk value is 20;

[0022] When the homogenate volume is 410L≤490L, the gel risk value is 22;

[0023] When the homogenate volume is 490L≤570L, the gel risk value is 24;

[0024] When the homogenate volume is greater than 570 L, the gel risk value is 25.

[0025] For the moisture content of the positive electrode active material, if the moisture content of the positive electrode active material is ≤2500ppm, its gel risk value is an even number less than 25; if the moisture content of the positive electrode active material is >2500ppm, its gel risk value is 25.

[0026] More specifically, they include: when the moisture content of the positive electrode active material is ≤200ppm, the gel risk value is 0; when the moisture content of the positive electrode active material is ≤600ppm, the gel risk value increases by 4 for every 200ppm increase in the moisture content of the positive electrode active material; when the moisture content of the positive electrode active material is 600ppm<800ppm, the gel risk value is 16; when the moisture content of the positive electrode active material is 800ppm<1000ppm, the gel risk value is 18; when the moisture content of the positive electrode active material is ≤2500ppm, the gel risk value increases by 2 for every 500ppm increase in the moisture content of the positive electrode active material; when the moisture content of the positive electrode active material is >2500ppm, the gel risk value is 25.

[0027] More specifically, they include:

[0028] When the moisture content of the positive electrode active material is ≤200ppm, its gel risk value is 0;

[0029] When the moisture content of the positive electrode active material is 200ppm or less and ≤400ppm, the gel risk value is 4;

[0030] When the moisture content of the positive electrode active material is 400ppm or less and ≤ 600ppm, the gel risk value is 8;

[0031] When the moisture content of the positive electrode active material is 600ppm or less and ≤800ppm, the gel risk value is 16;

[0032] When the moisture content of the positive electrode active material is 800ppm<≤1000ppm, its gel risk value is 18;

[0033] When the moisture content of the positive electrode active material is 1000ppm or less and ≤1500ppm, the gel risk value is 20;

[0034] When the moisture content of the positive electrode active material is 1500ppm or less and ≤2000ppm, the gel risk value is 22;

[0035] When the moisture content of the positive electrode active material is 2000ppm or less and ≤2500ppm, the gel risk value is 24;

[0036] The moisture content of the positive electrode active material is greater than 2500ppm, and its gel risk value is 25.

[0037] As an example, but not a limitation to the protection scope of the present invention, the method for detecting the moisture content of the positive electrode active material of the present invention is the Karl Fischer method commonly used in the technical field.

[0038] For the fine powder rate of the positive electrode active material, if the fine powder rate of the positive electrode active material is ≤8%, its gel risk value is less than 25; if the fine powder rate of the positive electrode active material is greater than 8%, its gel risk value is 25; wherein, the fine powder rate of the positive electrode active material is the volume density of the fine powder with a particle size less than 1 μm in the positive electrode active material, using. As an example, but not limiting the scope of protection of the present invention, the method for determining the fine powder rate of the positive electrode active material of the present invention is the laser particle size analyzer method commonly used in the technical field, using a laser particle size analyzer to measure the particle size of the positive electrode active material, obtain a particle size distribution curve, and calculate (the system automatically obtains) the volume density of the fine powder with a particle size in the range of 0 to 1 μm.

[0039] More specifically, they include: when the fine powder rate of the positive electrode active material is ≤0.5%, the gel risk value is 0; when the fine powder rate of the positive electrode active material is ≤5.5%, the gel risk value increases by 2 for every 0.5% increase in the fine powder rate of the positive electrode active material; when the fine powder rate of the positive electrode active material is ≤7.5%, the gel risk value increases by 1 for every 0.5% increase in the fine powder rate of the positive electrode active material; when the fine powder rate of the positive electrode active material is 7.5%<≤8%, the gel risk value is 24.5; the fine powder rate of the positive electrode active material is>8%, the gel risk value is 25.

[0040] More specifically, they include:

[0041] When the fine powder rate of the positive electrode active material is ≤0.5%, its gel risk value is 0;

[0042] When the fine powder rate of the positive electrode active material is 0.5% or less than 1%, the gel risk value is 2;

[0043] When the fine powder rate of positive electrode active material is 1%<≤1.5%, the gel risk value is 4;

[0044] When the fine powder rate of the positive electrode active material is 1.5% or less and the gel risk value is 6;

[0045] When the fine powder rate of positive electrode active material is 2%<≤2.5%, the gel risk value is 8;

[0046] When the fine powder rate of the positive electrode active material is 2.5% or less and ≤ 3%, the gel risk value is 10;

[0047] When the fine powder rate of positive electrode active material is 3%<≤3.5%, the gel risk value is 12;

[0048] When the fine powder rate of positive electrode active material is 3.5% or less and ≤4%, the gel risk value is 14;

[0049] When the fine powder rate of positive electrode active material is 4%<≤4.5%, the gel risk value is 16;

[0050] 4.5%<When the fine powder rate of positive electrode active material is ≤5%, its gel risk value is 18;

[0051] 5%<When the fine powder rate of positive electrode active material is ≤5.5%, its gel risk value is 20;

[0052] When the fine powder rate of the positive electrode active material is 5.5% or less and ≤ 6%, the gel risk value is 21;

[0053] When the fine powder rate of the positive electrode active material is 6% or less and the gel risk value is 22;

[0054] When the fine powder rate of the positive electrode active material is 6.5% or less and ≤7%, the gel risk value is 23;

[0055] 7%<When the fine powder rate of positive electrode active material is ≤7.5%, its gel risk value is 24;

[0056] When the fine powder rate of the positive electrode active material is 7.5% or less and ≤ 8%, the gel risk value is 24.5;

[0057] The fine powder rate of the positive electrode active material is greater than 8%, and its gel risk value is 25.

[0058] For the pH of the positive electrode active material, the pH of the positive electrode active material is ≤12.7, and its gel risk value is an even number less than 25; the pH of the positive electrode active material is greater than 12.7, and its gel risk value is 25; wherein, when measuring the pH of the positive electrode active material, the actual measured object is a mixture of the positive electrode active material and deionized water, wherein the mass ratio of the positive electrode active material to the deionized water is 1:10 to 1:30, preferably 1:20. When the mass ratio of the positive electrode active material to the deionized water is between 1:10 and 1:30, the measured pH deviation is between 0.1 and 0.2, and the influence on the determination of the gel risk value and the gel risk index is within the tolerance range.

[0059] More specifically, they include: when the pH of the positive electrode active material is less than 10, the gel risk value is 0; when the pH of the positive electrode active material is 10≤≤10.5, the gel risk value is 2; when the pH of the positive electrode active material is ≤11.5, the gel risk value increases by 4 for every 0.5 increase in the pH of the positive electrode active material; when the pH of the positive electrode active material is ≤12.4, the gel risk value increases by 4 for every 0.3 increase in the pH of the positive electrode active material; when the pH of the positive electrode active material is 12.4<12.7, the gel risk value is 24; and when the pH of the positive electrode active material is greater than 12.7, the gel risk value is 25.

[0060] More specifically, they include:

[0061] When the pH of the positive electrode active material is less than 10, its gel risk value is 0;

[0062] 10≤When the pH of the positive electrode active material is ≤10.5, its gel risk value is 2;

[0063] 10.5<When the pH of the positive electrode active material is ≤11, its gel risk value is 6;

[0064] 11<When the pH of the positive electrode active material is ≤11.5, its gel risk value is 10;

[0065] When the pH value of the positive electrode active material is 11.5<≤11.8, the gel risk value is 14;

[0066] 11.8<When the pH of the positive electrode active material is ≤12.1, its gel risk value is 18;

[0067] 12.1<When the pH of the positive electrode active material is ≤12.4, its gel risk value is 22;

[0068] 12.4<When the pH of the positive electrode active material is ≤12.7, its gel risk value is 24;

[0069] The pH of the positive electrode active material is greater than 12.7, and its gel risk value is 25.

[0070] According to actual experimental exploration and verification, the gel risk index corresponding to the risk degree of gel transformation of different positive electrode slurries is obtained, and the following contents are obtained, in order:

[0071] When the gel risk index is less than 20, the gel risk of the slurry is "no gel", and there is no need to add acid to antagonize the gelation trend;

[0072] When the gel risk index is 20≤<30, the gel risk of the slurry is “generally non-gel” and no acid needs to be added to antagonize the gelation trend;

[0073] When the gel risk index is 30≤<50, the gel risk of the slurry is “general gel risk” and acid needs to be added to antagonize the gelation trend;

[0074] When the gel risk index is 50≤<80, the gel risk of the slurry is "medium gel risk" and acid needs to be added to antagonize the gelation trend;

[0075] When the gel risk index is 80≤<90, the gel risk of the slurry is "large gel risk", and acid needs to be added to antagonize the gelation trend;

[0076] When the gel risk index is 90≤≤100, the slurry gel risk is "extreme gel risk" and acid needs to be added to antagonize the gelation trend.

[0077] S2. Determine the amount of acid added for pulping based on the risk of slurry gelation. The amount of acid added for pulping = mass of positive electrode active material × recommended acid value. The recommended acid value is ≤0.8%.

[0078] According to actual experimental exploration and verification, the amount of slurry acid added to the positive electrode slurry with different gel risk indexes can antagonize the gelation trend without reducing the electrical properties of the positive electrode active material and the coating effect of the positive electrode slurry, which are as follows: when the gel risk index is less than 30, the recommended acid addition value is 0; when the gel risk index is less than 90, the recommended acid addition value is increased by 0.1% for every increase of 10 in the gel risk index; when the gel risk index is 90≤<100, the recommended acid addition value is 0.8%.

[0079] More specifically, they include:

[0080] The gel risk index is less than 30, and the recommended acid value is 0;

[0081] 30≤Gel risk index<40, the recommended acid value is 0.1%;

[0082] 40≤Gel risk index<50, the recommended acid value is 0.2%;

[0083] 50≤Gel risk index<60, the recommended acid value is 0.3%;

[0084] 60≤Gel risk index<70, the recommended acid value is 0.4%;

[0085] 70≤Gel risk index<80, the recommended acid value is 0.5%;

[0086] 80≤Gel risk index<90, the recommended acid value is 0.6%;

[0087] 90≤Gel risk index≤100, the recommended acid value is 0.8%.

[0088] With the above technical solution, when predicting the gel risk of the slurry, first measure the actual values of each risk factor, find the corresponding gel risk values, and then sum them up to obtain the gel risk index of the positive electrode slurry; according to the gel risk index, quickly predict the gel risk of the slurry, judge the amount of acid added during pulping, add acid according to the amount of acid added during pulping, and then perform homogenization, which can antagonize the gelation trend of the positive electrode slurry and prevent excessive acid from affecting the electrical performance of the positive electrode active material and the coating effect of the positive electrode slurry.

[0089] The positive electrode slurry suitable for judging and predicting the gel risk of the slurry and judging the amount of acid added during pulping includes: positive electrode active material, binder, conductive agent and solvent. The solid content of the positive electrode slurry is 55-75 wt%, the positive electrode active material accounts for 50 wt%-70 wt%, the binder accounts for 2 wt%-5 wt%, and the conductive agent accounts for 1 wt-4 wt%.

[0090] The positive electrode active material includes sodium-based layered transition metal oxide with the chemical formula Na x Ni a Fe b Mn c M d O2, where: 0.6 < x < 1.2, a > 0, b > 0, c > 0, d ≥ 0, a + b + c + d = 1, and M includes at least one element from Group IA-VA and Group IB-VIIB.

[0091] The phase structure of the positive electrode active material includes at least one of O3 phase, O2 phase, P2 phase and P3 phase, the morphological characteristics include at least one of single crystal and polycrystal, the space group includes at least one of R3m and P63 / mmc, and the particle size range is: D50 = 3.5-9.5 μm, D90 < 35 μm. The content of the positive electrode active material in the positive electrode slurry is 50%-70 wt%.

[0092] The binder includes PVDF, the conductive agent includes at least one of acetylene black, carbon nanotubes, conductive carbon black and graphene, and the solvent includes NMP.

[0093] The acid used to antagonize the gelation of the positive electrode slurry includes at least one of maleic acid, oxalic acid, acetic acid and citric acid.

[0094] In practical applications, in order to ensure the stability and quality of the positive electrode slurry, in addition to judging the amount of acid added during pulping according to the above method and adding it to the positive electrode slurry, other factors that may affect the gel risk of the slurry need to be considered. For example, changes in environmental temperature and humidity may affect the stability of the slurry. Therefore, during the pulping process, the environmental conditions should be ensured to be within an appropriate range to reduce the influence of external factors on the stability of the slurry.

[0095] The beneficial effects of the present invention are as follows: based on experimental exploration and verification, the method provides the possibility of quickly predicting the slurry gel risk and judging the amount of acid added in slurrying in large-scale slurrying of sodium positive electrode layered oxide materials, which is used to antagonize the gelation trend of the positive electrode slurry and prevent excessive acid from affecting the electrical properties of the positive electrode active material and the coating effect of the positive electrode slurry; the method does not need to use the traditional titration method for measuring residual alkali or small-batch homogenization testing, but only needs to perform basic physical property testing, thereby improving the preparation efficiency and quality of the sodium positive electrode layered oxide material slurry. DETAILED DESCRIPTION

[0096] The present invention will be further described below in conjunction with embodiments:

[0097] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and comparative examples, and are not intended to limit the scope of protection of the present invention. It should be particularly noted that there may be multiple names for the same organic structure, as long as the structure is within the scope of this patent, it belongs to the protection object of this patent.

[0098] Unless otherwise defined, the raw materials, reagents, etc. in the following examples can be purchased from the market or prepared according to reported methods.

[0099] Generally, the gelation of PVDF-containing slurry includes three possible stages: the rate of the first stage is slow, the content of this base has not yet increased to the saturation point, although PVDF is undergoing defluorination, but the cross-linking is still slow; the rate of the second stage increases exponentially, at this time there is a high concentration of C=C structure, and cross-linking occurs easily; the rate of the third stage is slow, because as defluorination and cross-linking occur, the amount of C=C decreases and the cross-linking rate is slow.

[0100] Generally, the risk of degelling the PVDF-containing slurry can be determined if the slurry does not produce a jelly-like gel that cannot be eliminated by stirring during homogenization or within half an hour after homogenization, or if the viscosity increase of the slurry is less than 25% within half an hour after homogenization.

[0101] Example 1

[0102] (1) Determine the amount of acid added in pulping

[0103] The homogenate volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenate volume was 150 L, and the moisture content of the positive electrode active material was measured to be 156 ppm, the fine powder rate was 0%, and the pH was 11.5.

[0104] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 8, the gel risk value of the moisture content of the positive electrode active material was 0, the gel risk value of the fine powder rate was 0, and the gel risk value of pH was 10.

[0105] The calculated gel risk index of the positive electrode slurry is 18, so the slurry gel risk is "no gel", and no acid needs to be added to prevent gelation.

[0106] (2) Homogenate test

[0107] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 56%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 4268 mPa·s.

[0108] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 4330 mPa·s. After being allowed to stand for 30 minutes, the viscosity A2 was measured to be 4329 mPa·s.

[0109] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=1.5%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=1.4%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0110] (3) Coating test: The coating effect is good.

[0111] Example 2

[0112] (1) Determine the amount of acid added in pulping

[0113] The homogenate volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenate volume was 150 L, and the moisture content of the positive electrode active material was measured to be 121 ppm, the fine powder rate was 1.1%, and the pH was 11.4.

[0114] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 8, the gel risk value of the moisture content of the positive electrode active material was 0, the gel risk value of the fine powder rate was 4, and the gel risk value of pH was 10.

[0115] The calculated gel risk index of the positive electrode slurry is 22, so the slurry gel risk is "generally no gel", and no acid needs to be added to prevent gelation.

[0116] (2) Homogenate test

[0117] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 58%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5001 mPa·s.

[0118] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5058 mPa·s. After being allowed to stand for 30 minutes, the viscosity A2 was measured to be 5100 mPa·s.

[0119] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=1.1%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=2.0%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0120] (3) Coating test: The coating effect is good.

[0121] Example 3

[0122] (1) Determine the amount of acid added in pulping

[0123] The homogenate volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenate volume was 200 L, and the moisture content of the positive electrode active material was measured to be 400 ppm, the fine powder rate was 0.8%, and the pH was 11.7.

[0124] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 16, the gel risk value of the moisture content of the positive electrode active material was 4, the gel risk value of the fine powder rate was 2, and the gel risk value of pH was 14.

[0125] The calculated gel risk index of the positive electrode slurry is 36, so the slurry gel risk is "general gel risk", and the recommended acid addition value is 0.1%. The recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0126] (2) Homogenate test

[0127] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 60%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5126 mPa·s.

[0128] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5864 mPa·s. After being allowed to stand for 30 minutes, the viscosity A2 was measured to be 5512 mPa·s.

[0129] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=14.4%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=7.5%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0130] (3) Coating test: The coating effect is good.

[0131] Comparative Example 1

[0132] Compared with Example 3, the difference of Comparative Example 1 is only that no maleic acid is added.

[0133] The homogenate test record is:

[0134] The solid content of the positive electrode slurry is 59.9%. After homogenization, the initial viscosity A0 is measured to be 5944 mPa·s; after the positive electrode slurry is allowed to stand for 5 minutes, the viscosity A1 is measured to be 7047 mPa·s; after standing for 30 minutes, the viscosity A2 is measured to be 8339 mPa·s.

[0135] Calculated separately: the viscosity increase after standing for 5 minutes: (A1-A0) / A0=18.6%, the viscosity increase after standing for 30 minutes: (A2-A0) / A0=40.3%, the viscosity increase is greater than 25%, and after stirring the positive electrode slurry again, its viscosity cannot be restored, that is, the positive electrode slurry undergoes irreversible gelation.

[0136] Example 4

[0137] (1) Determine the amount of acid added in pulping

[0138] The amount of homogenate was determined, and the physical properties of the positive electrode active material to be slurried were tested: the amount of homogenate was 180 L, and the moisture content of the positive electrode active material was measured to be 424 ppm, the fine powder rate was 1.7%, and the pH was 11.5.

[0139] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 16, the gel risk value of the moisture content of the positive electrode active material was 8, the gel risk value of the fine powder rate was 6, and the gel risk value of pH was 10.

[0140] The calculated gel risk index of the positive electrode slurry is 40, so the slurry gel risk is "general gel risk", and the recommended acid addition value is 0.2%. The recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0141] (2) Homogenate test

[0142] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 62%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5220 mPa·s.

[0143] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5324 mPa·s. After it was allowed to stand for 30 minutes, the viscosity A2 was measured to be 5557 mPa·s.

[0144] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=2%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=6.5%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0145] (3) Coating test: The coating effect is good.

[0146] Comparative Example 2

[0147] Compared with Example 4, the difference of Comparative Example 2 is only that no maleic acid is added.

[0148] The homogenization test record is: the solid content of the positive electrode slurry is 61.8%. After the homogenization is completed, the positive electrode slurry produces a jelly-like gel during the viscosity test, and the jelly-like gel cannot be removed by stirring, that is, the positive electrode slurry undergoes irreversible gelation.

[0149] Example 5

[0150] (1) Determine the amount of acid added in pulping

[0151] The homogenate volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenate volume was 300 L, and the moisture content of the positive electrode active material was measured to be 802 ppm, the fine powder rate was 0%, and the pH was 11.8.

[0152] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 18, the gel risk value of the moisture content of the positive electrode active material was 18, the gel risk value of the fine powder rate was 0, and the gel risk value of pH was 14.

[0153] The calculated gel risk index of the positive electrode slurry = 50, so the slurry gel risk is "medium gel risk", the recommended acid addition value is 0.3%, and the recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0154] (2) Homogenate test

[0155] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 64%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5639 mPa·s.

[0156] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5881 mPa·s. After it was allowed to stand for 30 minutes, the viscosity A2 was measured to be 6259 mPa·s.

[0157] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=4.3%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=11%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0158] (3) Coating test: The coating effect is good.

[0159] Comparative Example 3

[0160] Compared with Example 5, the difference of Comparative Example 3 is only that no maleic acid is added.

[0161] The homogenization test record is: the solid content of the positive electrode slurry is 63.7%. After the homogenization is completed, the positive electrode slurry produces a jelly-like gel during the viscosity test, and the jelly-like gel cannot be removed by stirring, that is, the positive electrode slurry undergoes irreversible gelation.

[0162] Example 6

[0163] (1) Determine the amount of acid added in pulping

[0164] The homogenization volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenization volume was 420 L, and the moisture content of the positive electrode active material was measured to be 678 ppm, the fine powder rate was 2.6%, and the pH was 11.6.

[0165] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 22, the gel risk value of the moisture content of the positive electrode active material was 16, the gel risk value of the fine powder rate was 10, and the gel risk value of pH was 14.

[0166] The calculated gel risk index of the positive electrode slurry is 62, so the slurry gel risk is "medium gel risk", and the recommended acid addition value is 0.4%. The recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0167] (2) Homogenate test

[0168] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 66%, and no jelly-like gel appears. The initial viscosity A0=4990 mPa·s is measured.

[0169] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5812 mPa·s. After it was allowed to stand for 30 minutes, the viscosity A2 was measured to be 5894 mPa·s.

[0170] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=16.5%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=18.1%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0171] (3) Coating test: The coating effect is good.

[0172] Comparative Example 4

[0173] Compared with Example 6, the difference of Comparative Example 4 is only that no maleic acid is added.

[0174] The homogenization test record is: the solid content of the positive electrode slurry is 65.6%. After the homogenization is completed, the positive electrode slurry produces a jelly-like gel during the viscosity test, and the jelly-like gel cannot be removed by stirring, that is, the positive electrode slurry undergoes irreversible gelation.

[0175] Example 7

[0176] (1) Determine the amount of acid added in pulping

[0177] The homogenization volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenization volume was 500 L, and the moisture content of the positive electrode active material was measured to be 888 ppm, the fine powder rate was 4.3%, and the pH was 11.6.

[0178] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 24, the gel risk value of the moisture content of the positive electrode active material was 18, the gel risk value of the fine powder rate was 16, and the gel risk value of pH was 14.

[0179] The calculated gel risk index of the positive electrode slurry is 72, so the slurry gel risk is "medium gel risk", and the recommended acid addition value is 0.5%. The recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0180] (2) Homogenate test

[0181] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 68%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5334 mPa·s.

[0182] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5399 mPa·s. After it was allowed to stand for 30 minutes, the viscosity A2 was measured to be 5969 mPa·s.

[0183] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=1.0%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=11.7%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0184] (3) Coating test: The coating effect is good.

[0185] Comparative Example 5

[0186] Compared with Example 7, the difference of Comparative Example 5 is only that no maleic acid is added.

[0187] The homogenization test record is: the solid content of the positive electrode slurry is 67.5%. After the homogenization is completed, the positive electrode slurry produces a jelly-like gel during the viscosity test, and the jelly-like gel cannot be removed by stirring, that is, the positive electrode slurry undergoes irreversible gelation.

[0188] Example 8

[0189] (1) Determine the amount of acid added in pulping

[0190] The homogenization volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenization volume was 650 L, and the moisture content of the positive electrode active material was measured to be 1514 ppm, the fine powder rate was 5.2%, and the pH was 11.7.

[0191] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 25, the gel risk value of the moisture content of the positive electrode active material was 22, the gel risk value of the fine powder rate was 20, and the gel risk value of pH was 14.

[0192] The calculated gel risk index of the positive electrode slurry is 81, so the slurry gel risk is "large gel risk", and the recommended acid addition value is 0.6%. The recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0193] (2) Homogenate test

[0194] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 70%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5543 mPa·s.

[0195] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 6213 mPa·s. After it was allowed to stand for 30 minutes, the viscosity A2 was measured to be 6877 mPa·s.

[0196] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=12.1%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=24.1%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0197] (3) Coating test: The coating effect is good.

[0198] Comparative Example 6

[0199] Compared with Example 8, the difference of Comparative Example 6 is only that no maleic acid is added.

[0200] The homogenization test record is: the solid content of the positive electrode slurry is 69.4%. After the homogenization is completed, the positive electrode slurry produces a jelly-like gel during the viscosity test, and the jelly-like gel cannot be removed by stirring, that is, the positive electrode slurry undergoes irreversible gelation.

[0201] Example 9

[0202] (1) Determine the amount of acid added in pulping

[0203] The homogenization volume was determined, and the physical properties of the positive electrode active material to be slurried were tested: the homogenization volume was 550 L, and the moisture content of the positive electrode active material was measured to be 1650 ppm, the fine powder rate was 5.7%, and the pH was 12.5.

[0204] The gel risk value of each risk factor was determined: the gel risk value of the homogenate amount was 24, the gel risk value of the moisture content of the positive electrode active material was 22, the gel risk value of the fine powder rate was 21, and the gel risk value of pH was 24.

[0205] The calculated gel risk index of the positive electrode slurry is 91, so the slurry gel risk is "large gel risk", and the recommended acid addition value is 0.8%. The recommended acid addition amount = the mass of the positive electrode active material × the recommended acid addition value.

[0206] (2) Homogenate test

[0207] Homogenization: Add PVDF and NMP into a stirring device and stir for 240 min. Add the conductive agent SP and the above-recommended acid addition amount of maleic acid into the stirring device and stir for 60 min. Add the positive electrode active material (sodium-based transition metal oxide) into the stirring device in two steps and stir for 60 min. At this time, the solid content of the positive electrode slurry is 72%, and no jelly-like gel appears. The initial viscosity A0 is measured to be 5121 mPa·s.

[0208] After the positive electrode slurry was allowed to stand for 5 minutes, the viscosity A1 was measured to be 5564 mPa·s. After being allowed to stand for 30 minutes, the viscosity A2 was measured to be 5521 mPa·s.

[0209] The viscosity increase after standing for 5 minutes was calculated as follows: (A1-A0) / A0=8.7%, and the viscosity increase after standing for 30 minutes was calculated as follows: (A2-A0) / A0=7.8%, both of which were less than 25%, indicating that the slurry had a risk of degelling.

[0210] (3) Coating test: The coating effect is good.

[0211] Comparative Example 7

[0212] Compared with Example 9, the difference of Comparative Example 7 is only that no maleic acid is added.

[0213] The homogenization test record is: the solid content of the positive electrode slurry is 71.2%. After the homogenization is completed, the positive electrode slurry produces a jelly-like gel during the viscosity test, and the jelly-like gel cannot be removed by stirring, that is, the positive electrode slurry undergoes irreversible gelation.

[0214] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for quickly determining the amount of acid added in the pulping of sodium positive electrode layered oxide materials, characterized in that: Predicting the slurry gel risk based on risk factors, including: slurry volume, as well as the moisture content, fine powder rate and pH of the positive electrode active material; The amount of acid added for pulping is determined based on the risk of slurry gelation. The amount of acid added for pulping = the mass of positive electrode active material × recommended acid value. The recommended acid value is ≤0.8%.

2. The method for quickly determining the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 1, characterized in that: The gel risk of slurry is predicted by the gel risk index, which is the sum of the gel risk values ​​of each risk factor.

3. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 2, characterized in that: The gel risk value of each risk factor is a real number ranging from 0 to 25.

4. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 3, characterized in that: The homogenate volume is ≤570L, and the gel risk value is an even number less than 25, including: When the homogenate volume is ≤10L, the gel risk value is 0. When the homogenate volume is ≤170L, the gel risk value increases by 4 for every 80L increase in the homogenate volume. When the homogenate volume is 170L or less and the gel risk value is 16, When the homogenate volume is ≤570L, the gel risk value increases by 2 for every 80L increase in the homogenate volume; The homogenate volume is >570L, and the gel risk value is 25.

5. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 3, characterized in that: The moisture content of the positive electrode active material is ≤2500ppm, and its gel risk value is an even number less than 25, including: When the moisture content of the positive electrode active material is ≤200ppm, its gel risk value is 0. When the moisture content of the positive electrode active material is ≤600ppm, the gel risk value increases by 4 for every 200ppm increase in the moisture content of the positive electrode active material. When the moisture content of the positive electrode active material is 600ppm<≤800ppm, the gel risk value is 16; when the moisture content of the positive electrode active material is 800ppm<≤1000ppm, the gel risk value is 18. When the moisture content of the positive electrode active material is ≤2500ppm, the gel risk value increases by 2 for every 500ppm increase in the moisture content of the positive electrode active material; The moisture content of the positive electrode active material is greater than 2500ppm, and its gel risk value is 25.

6. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 3, characterized in that: The fine powder rate of the positive electrode active material is ≤8%, and its gel risk value is less than 25, including: When the fine powder rate of the positive electrode active material is ≤0.5%, its gel risk value is 0. When the fine powder rate of the positive electrode active material is ≤5.5%, the gel risk value increases by 2 for every 0.5% increase in the fine powder rate of the positive electrode active material. When the fine powder rate of the positive electrode active material is ≤7.5%, the gel risk value increases by 1 for every 0.5% increase in the fine powder rate of the positive electrode active material. When the fine powder rate of the positive electrode active material is 7.5% or less and ≤ 8%, the gel risk value is 24.5; The fine powder rate of the positive electrode active material is greater than 8%, and its gel risk value is 25.

7. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 6, characterized in that: The fine powder rate of the positive electrode active material is the volume density of fine powder having a particle size of less than 1 μm in the positive electrode active material.

8. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to claim 3, characterized in that: The pH of the positive electrode active material is ≤12.7, and its gel risk value is an even number less than 25, including: When the pH of the positive electrode active material is less than 10, its gel risk value is 0. 10≤When the pH value of the positive electrode active material is ≤10.5, its gel risk value is 2. When the pH of the positive electrode active material is ≤11.5, the gel risk value increases by 4 for every 0.5 increase in the pH of the positive electrode active material. When the pH of the positive electrode active material is ≤12.4, the gel risk value of the positive electrode active material increases by 4 for every 0.3 increase in pH; 12.4<When the pH of the positive electrode active material is ≤12.7, its gel risk value is 24; The pH of the positive electrode active material is greater than 12.7, and its gel risk value is 25.

9. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to any one of claims 2 to 8, characterized in that: Including in order: When the gel risk index is less than 30, the recommended acid addition value is 0, where: when the gel risk index is less than 20, the slurry gel risk is "no gel", and when the gel risk index is 20≤<30, the slurry gel risk is "generally no gel"; When the gel risk index is less than 90, it is recommended to increase the acid value by 0.1% for every 10 increase in the gel risk index, among which: when the gel risk index is 30≤<50, the slurry gel risk is "general gel risk", when the gel risk index is 50≤<80, the slurry gel risk is "medium gel risk", and when the gel risk index is 80≤<90, the slurry gel risk is "large gel risk"; When the gel risk index is 90≤<100, the gel risk of the slurry is "extreme gel risk" and the recommended acid addition value is 0.8%.

10. The method for quickly judging the amount of acid added in pulping of sodium positive electrode layered oxide materials according to any one of claims 1 to 9, characterized in that: When the sodium positive electrode layered oxide material is pulped, the pulping raw materials include positive electrode active material, binder, conductive agent, solvent and acid, the positive electrode active material includes sodium-based layered transition metal oxide, the binder includes PVDF, the conductive agent includes at least one of acetylene black, carbon nanotubes, conductive carbon black and graphene, the solvent includes NMP, and the acid includes at least one of maleic acid, oxalic acid, acetic acid and citric acid; When the pH of the positive electrode active material is detected, the mass ratio of the positive electrode active material to the deionized water in the object to be detected is 1:10 to 1:30.

Citation Information

Cited By

  • Method and equipment for rapidly judging pulping acid adding amount of sodium-ion battery positive electrode material

    CN121215128A

  • Method and equipment for quickly determining the amount of acid added during slurry preparation of a sodium-ion battery cathode material

    CN121215128B